Two new species of Pseudonannolene Silvestri, 1895 from razilian limestone caves (Spirostreptida: seudonannolenidae): synotopy of a troglophilic and a troglobiotic species - Iniesta, Luiz Felipe Moretti; Ferreira, Rodrigo Lopes (Zootaxa, 2013)
Pseudonannolene ambuatinga n. sp. and Pseudonannolene saguassu n. sp. are described from individuals collected in limestone caves in the municipality of Pains, Minas Gerais, Brazil, which comprises a scenario of great conflict between speleological preservation and limestone extraction. The two species differ in their gonopod morphology and in size and color. Pseudonannolene ambuatinga n. sp. is regarded as the second troglobite species known for the family. This is the first report for Brazil of syntopy in two congeneric species in the same cave.